2013
DOI: 10.3201/eid1902.120834
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley Fever, Sudan, 2007 and 2010

Abstract: Viral sequences analyzed indicate recent virus movement and support the need for surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 30 publications
0
56
1
2
Order By: Relevance
“…Other studies have reported higher rates [32,44]: for example, estimates from Aradaib et al . [44] were 4.20 × 10 −4 , 5.06 × 10 −4 , and 4.29 × 10 −4 substitutions per site per year for S, M, and L, respectively; the 95% HPD intervals reported in that paper overlap with ours. These differences might be a result of the different datasets used: our work should have better resolution because the dataset is larger and more diverse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported higher rates [32,44]: for example, estimates from Aradaib et al . [44] were 4.20 × 10 −4 , 5.06 × 10 −4 , and 4.29 × 10 −4 substitutions per site per year for S, M, and L, respectively; the 95% HPD intervals reported in that paper overlap with ours. These differences might be a result of the different datasets used: our work should have better resolution because the dataset is larger and more diverse.…”
Section: Discussionmentioning
confidence: 99%
“…The Aradaib et al . [44] study was also limited to only two lineages of the 11 in our analysis, and covered only strains from Kenya, Sudan, Madagascar, and Zimbabwe. Interestingly, Freire et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This considers the first report of the disease occurrence outside the African continent-where it had been confined so far-becoming a threat to the Middle East. In 2007, there were outbreaks in Kenya, Somalia, and Tanzania [4,5], while in 2008 and 2010, recent outbreaks of RFV occurred in Sudan [6,7]. In the year 2000, Saudi Arabia and Yemen were exposed to a huge RVF outbreak [8,9].…”
Section: Rvf Is An Office International Des Epizooties (Oie)-listedmentioning
confidence: 99%
“…2,3 Congo-Crimean hemorrhagic fever (CCHF), West Nile virus (WNV), and chikungunya are known to occur in southern Sudan, on the border with South Sudan and Rift Valley fever (RVF) has occurred in South Sudan itself. [4][5][6][7] Importantly, RVF virus circulates sporadically or even cyclically, while most other agents of acute febrile illness circulate seasonally or continuously. Leptospirosis is known to occur in South Sudan.…”
mentioning
confidence: 99%